Deformation and Fluid-Rock Interaction in the Supra-subduction Mantle: Microstructures and Water Contents in Peridotite Xenoliths from the Avacha Volcano, Kamchatka - Soustelle, Vincent; Tommasi, Andrea; Demouchy, Sylvie; Ionov, Dmitri (Journal of Petrology, 2010)
International audience The mantle above a subducting slab is the site of complex interactions between deformation, partial melting, fluid migration and magma transport. To constrain these interactions and their effects on olivine deformation, we analyze microstructures, crystal preferred orientations, and water contents of peridotite xenoliths entrained by andesites of the Avacha volcano, southern Kamchatka arc. These xenoliths are refractory spinel harzburgites that have coarse-grained microstructures with widely spaced subgrain boundaries and sinuous grain boundaries in olivine, consistent with deformation by dislocation creep under low deviatoric stress (< 13 MPa) and with a significant contribution from diffusional processes. Analysis of crystal preferred orientations (CPO) indicates dominant activation of high-temperature, low-stress {0kl}[100] slip systems in olivine and of(100)[001] in orthopyroxene. In most samples, coarse opx crystals, elongated parallel to the lineation, enclose small olivine grains in crystallographic continuity with neighbouring crystals, indicating crystallization of orthopyroxene at the expense of olivine as a result of reactive percolation of Si-rich fluids coeval with the high-temperature deformation. Secondary crystallization of interstitial orthopyroxene led locally to development of opx-rich lenses parallel to the foliation, characterized by a decrease in olivine grain size and dispersion of the olivine CPO without changing the dominant slip systems. Half of the samples also show acicular orthopyroxene aggregates with which is associated a fine-grained matrix composed of rounded strain-free olivine, orthopyroxene, spinel, and rare amphibole crystals. This matrix occurs pervasively along grain boundaries or forms millimeter-scale irregular lenses and anastomosing veinlets that crosscut the coarse crystals and their ductile deformation structures. Both acicular orthopyroxene and the fine-grained matrix are interpreted as resulting from reactive transport of H2O-rich fluids ...